Racial Disparities in Age at Time of Homicide Victimization: A Test of the Multiple Disadvantage Model. (January 2015) - Lo, Celia C.; Howell, Rebecca J.; Cheng, Tyrone C.
This study sought the factors associated with race/ethnicity disparities in the age at which homicide deaths tend to occur. We used the multiple disadvantage model to take race into account as we evaluated associations between age at time of homicide victimization and several social structural, mental health−related, and lifestyle factors. Data were derived from the 1993 National Mortality Followback Survey, a cross-sectional interview study of spouses, next of kin, other relatives, and close friends of individuals 15 years and older who died in the United States in 1993. Our results showed age at time of homicide mortality to be related to the three types of factors; race moderated some of these relationships. In general, being employed, married, and a homeowner appeared associated with reduced victimization while young. The relationship of victimization age and employment was not uniform across racial groups, nor was the relationship of victimization age and marital status uniform across groups. Among Blacks, using mental health services was associated with longer life. Homicide by firearm proved important for our Black and Hispanic subsamples, while among Whites, alcohol's involvement in homicide exerted significant effects. Our results suggest that programs and policies serving the various racial/ethnic groups can alleviate multiple disadvantages relevant in homicide victimization at an early age.